Implementasi Metodologi Waterfall Pada Pengembangan Sistem Manajemen Data Posyandu Berbasis Framework Codeigniter - Septianita, Septianita; Noprisson, Handrie (JSAI (Journal Scientific and Applied Informatics), 2024)
Integrated Service Post (Posyandu) as a community institution serving villages and urban areas plays a crucial role in conducting activities that transfer health knowledge and provide healthcare services. Various information technology-based Posyandu platforms have been developed across different regions, offering a diverse range of features. However, there has yet to be comprehensive and holistic research discussing the developed Posyandu platform models. This study aims to develop a standard platform for the Digital Move Posyandu application (Posyandu-DM) to support Posyandu management in Indonesia. Using the waterfall methodology, this research is conducted from October 2023 to June 2024 through the stages of systematic literature review, needs analysis, model design, implementation, testing, and application maintenance. Posyandu-DM is designed to provide key features such as registration, health checks, reporting, mapping, and education. Evaluation is conducted using the ServQual method, which assesses the dimensions of information quality, efficiency, and reliability, yielding scores of 4.1, 4.3, and 4.2, respectively. These results indicate that the application is performing reasonably well but requires some improvements, particularly regarding interface personalization for elderly users.